Phytochemical Delivery Through Transferosome (Phytosome): An Advanced Transdermal Drug Delivery for Complementary Medicines - Chen, Rong-Ping; Chavda, Vivek P.; Patel, Aayushi B.; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2022)
Transdermal drug delivery aims to create a safe and effective method of administering drugs through the skin that attracts a lot of attention and investment due to the constant progress in the field. Transferosomes are flexible or malleable vesicles (having almost the same structure as liposomes but with better skin penetration properties) discovered initially in the early 90s. The name transferosomes, which means "carrying bodies," is coined from the Latin phrase "Transferee," which means "to carry through," and the Greek term "soma," meaning "body." In comparison to typical herbal extracts, phytosomes (Transferosomes) are created by attaching specific herbal extracts to phosphatidylcholine, resulting in a formulation with increased solubility and, hence, better absorption, resulting in improved pharmacokinetic and pharmacodynamic features of the entrapped drugs. We are using the word phytosomes and transferosomes interchangeably. In this mini-review, we have demonstrated the enormous potential of developing nanotechnology to deliver bioactive phytochemicals, with a special emphasis on phytosomes (Transferosomes) as a unique lipid-based nanocarrier for transdermal drug delivery.